Clinical and Cost Burden of Primary Sjögren’s Syndrome: Descriptive Analysis Using a US Administrative Claims Database - Sue Perera; Liyuan Ma; Raj Punwaney; Sulabha Ramachandran (Journal of Health Economics and Outcomes Research)
# Background Current knowledge of the disease burden of primary Sjögren’s syndrome (pSS) is limited.